Design, Fabrication And Experimental Evaluation Of Parabolic Trough Solar Concentrator At Bangi, Malaysia - Ibrahim Magaji Kotorkoshi (Universiti Sains Islam Malaysia, 2024)
3130064 (FST) - CHAPTER 4 (missing page 49-52)